Decadal variability in mid-atmosphere temperature derived from continuous lidar observations - Pedro Da Costa Louro; Philippe Keckhut; Alain Hauchecorne; Robin Wing; Gerd Baumgarten; Michael Gerding; Thierry Leblanc; Bernd Kaifler; Natalie Kaifler; Wolfgang Steinbrecht; Ali Jalali; Robert J. Sica (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Multiple Lineages of Transmissible Neoplasia in the Basket Cockle ( C. nuttallii ) With Repeated Horizontal Transfer of Mitochondrial DNA - Marisa A. Yonemitsu; Jordana K. Sevigny; Lauren E. Vandepas; James L. Dimond; Rachael M. Giersch; Helen J. Gurney‐Smith; Cathryn L. Abbott; Janine Supernault; Ruth Withler; Peter D. Smith; Sydney A. Weinandt; Fiona E. S. Garrett; et al. (Molecular Ecology, 2025)
Transmissible cancers are clonal lineages of neoplastic cells able to infect multiple hosts, spreading through populations in the environment as an infectious disease. Transmissible cancers have been identified in Tasmanian devils, dogs, and bivalves. Several lineages of bivalve transmissible neoplasias (BTN) have been identified in multiple bivalve species. In 2019 in Puget Sound, Washington, USA, disseminated neoplasia was observed in basket cockles ( Clinocardium nuttallii ), a species that is important to the culture and diet of the Suquamish Tribe as well as other tribes with traditional access to the species. To test whether disseminated neoplasia in cockles is a previously unknown lineage of BTN, a nuclear locus was amplified from cockles from Agate Pass, Washington, and sequences revealed evidence of transmissible cancer in several individuals. We used a combination of cytology and quantitative PCR to screen collections of cockles from 11 locations in Puget Sound and along the Washington coastline to identify the extent of contagious cancer spread in this species. Two BTN lineages were identified in these cockles, with one of those lineages (CnuBTN1) being the most prevalent and geographically widespread. Within the CnuBTN1 lineage, multiple nuclear loci support the conclusion that all cancer samples form a single clonal lineage. However, the mitochondrial alleles in each cockle with CnuBTN1 are different from each other, suggesting mitochondrial genomes of this cancer have been replaced multiple times during its evolution, through horizontal transmission. The identification and analysis of these BTNs are critical for broodstock selection, management practices, and repopulation of declining cockle populations, which will enable continued cultural connection and dietary use of the cockles by Coast Salish Tribes.

Resolution of fluorescence in-situ hybridization mapping on rice mitotic prometaphase chromosomes, meiotic pachytene chromosomes and extended DNA fibers - Zhukuan Cheng; C. Robin Buell; Rod A. Wing; Jiming Jiang (Chromosome Research, 2002)